Imperfect Information and the Meltzer-Richard Hypothesis - Christian Bredemeier (Verein für Socialpolitik, 2010)
Standard models of voting on redistribution generate a clear-cut prediction: redistribution increases in income skewness. (the Meltzer-Richard hypothesis) Empirical evidence on this issue is mixed. Changes in income skewness are often accompanied by developments in redistribution into the opposite direction. This paper argues that it is important to distinguish between sources of changes in income skewness, polarization and upward mobility which both have the same impact on income skewness. In a model with imperfect information, these developments affect redistribution in different ways. While polarization generates a positive relation between income skewness and redistribution, upward mobility can have the opposite effect.
Keywords: D72; H24; D83; 330; Voting; Redistribution; Imperfect Information